Getting the best from the Heart Team: guidance for cardiac multidisciplinary meetings. Issue 11 (8th April 2022) - Archbold, Andrew; Akowuah, Enoch; Banning, Adrian P; Baumbach, Andreas; Braidley, Peter; Cooper, Graham; Kendall, Simon; MacCarthy, Philip; O'Kane, Peter; O'Keeffe, Niall; Shah, Benoy Nalin; Watt, Victoria; et al.
Abstract : The purpose of this document is to update the existing joint British Societies recommendations on multidisciplinary meetings (MDMs) published in 2015 to reflect changes in practice. We aim to provide guidance on the structure and function of MDMs which should be taking place in every cardiac surgical centre. Out of scope are MDMs that do not require the routine presence of a cardiac surgeon such as electrophysiology MDMs and those which are not provided in every centre, such as complex aortic surgery.